Insight Into the Effects of Nisin and Cecropin on the Oral Microbial Community of Rats by High-Throughput Sequencing - Wu, Lijuan; Li, Fei; Ran, Lisha; Gao, Yanping; Xie, Peijuan; Yang, Jian; Ke, Famin; Liu, Li; Wang, Qin; Gao, Xiaowei (Frontiers in Microbiology, 2020)
The oral microbiome can have major impact on oral health and disease. Antimicrobial peptides (AMPs), such as nisin and cecropin, have been widely used as food preservatives or feed additives, and are thus inevitably ingested by consumers from their oral cavity. However, as broad-spectrum antimicrobial reagents, the consequences of AMPs on the oral microbiome of consumers remain poorly characterized. In this study, we performed 16S rDNA gene-based high throughput sequencing to investigate the influences of nisin and cecropin on the oral microbial community of rats. Our results suggest that although nisin and cecropin have different effects on the oral microbiome of rats, both AMPs could impact the composition of oral microbial communities at both phylum and genus levels. Cecropin significantly reduced the diversity and richness of the rat oral microbial community. Notably, the relative abundance of the pathogen Acinetobacter baumannii was remarkably increased in the oral microbial community of rats bred with cecropin-containing feed. In addition, nisin significantly reduced the amount of immunoglobulin sIgA in saliva of rats.